2015
DOI: 10.1080/15287394.2015.1051204
|View full text |Cite
|
Sign up to set email alerts
|

Is There Sufficient Training of Health Care Staff on Noise Reduction in Neonatal Intensive Care Units? a Pilot Study From Neonoise Project

Abstract: Evidence indicates that exposure to high levels of noise adversely affects human health, and these effects are dependent upon various factors. In hospitals, there are many sources of noise, and high levels exert an impact on patients and staff, increasing both recovery time and stress, respectively. The goal of this pilot study was to develop, implement and evaluate the effectiveness of a training program (TP) on noise reduction in a Neonatal Intensive Care Units (NICU) by comparing the noise levels before and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 19 publications
2
36
0
5
Order By: Relevance
“…Kellam & Bhatia [34] suggested that human speech contribute to the spike in sound energy at 500 Hz. In addition, results described by Carvalhais et al [1] showed the same pattern. In fact, evidence shows a reduction in sound pressure levels predominantly above 400 Hz during the night, where there is a tendency to decrease conversation and alarm sounds [1,33].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Kellam & Bhatia [34] suggested that human speech contribute to the spike in sound energy at 500 Hz. In addition, results described by Carvalhais et al [1] showed the same pattern. In fact, evidence shows a reduction in sound pressure levels predominantly above 400 Hz during the night, where there is a tendency to decrease conversation and alarm sounds [1,33].…”
Section: Discussionsupporting
confidence: 72%
“…In general, noise was identified by healthcare professionals as an agent with a negative impact on the environment. Indeed, other studies in hospital context found similar data [1,29,30]. However, in a study conducted in an emergency department, 53% of the sample (only constituted by nurses) felt their cognitive function was never or rarely affected by noise [31].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Health professionals are aware about this issue and identified noise as an agent with a negative impact on work performance [6][7][8]. In fact, it is known that the hospital environment has many occupational health risks due to the variety of clinical and nonclinical tasks performed by healthcare workers.…”
Section: Source Of Noisementioning
confidence: 99%
“…To ensure that all the staff of the NICU under study such as physicians, nursing staff, and auxiliary staff attended the lecture (n = 79), 14 training sessions were given [2,6]. The lecture included (1) general concepts of noise; (2) the results of the sound pressure levels obtained in the first phase and the comparison of these to the recommended values suggested by WHO and other regulatory agencies; (3) the negative impact of noise on health, both for neonates and professionals; and (4) some actions that needed to be implemented to ensure noise reduction were undertaken [6]. Regarding these actions, health professionals had a significant role in the development of an action plan to address specific noise issues.…”
Section: Behavioral and Structural Modifications In Nicumentioning
confidence: 99%